2014
DOI: 10.1007/s10461-014-0830-z
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Acceptability of HIV Self-Testing Among Health Care Workers in Kenya

Abstract: Health care workers (HCWs) in sub-Saharan Africa are at a high risk of HIV infection from both sexual and occupational exposures. However, many do not seek HIV testing. This paper examines the acceptability of an unsupervised facility-based HIV self-testing (HIV-ST) intervention among HCWs and their partners and factors associated with uptake of HIVST among HCWs. HCWs in seven large Kenyan hospitals were invited to participate in pre-HIVST information sessions during which they were offered HIVST kits to take … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 8 publications
7
102
2
Order By: Relevance
“…The percentage of men out of total persons tested was reported in 25 home HTC studies 5,14,18,29,31,32,37,38,41–45,63,64,66,6872,8890 , two home with self-testing 11,75 , 10 mobile 10,13,68,72,9199 , 3 index partner 47,49,88 , 3 campaign 46,47,76 , 2 workplace 100,101 , 20 facility VCT 52,54,61,64,81,88,89,92,93,95,96,98,102107 , and 13 facility PITC 58,60,82–84,86,99,108113 (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of men out of total persons tested was reported in 25 home HTC studies 5,14,18,29,31,32,37,38,41–45,63,64,66,6872,8890 , two home with self-testing 11,75 , 10 mobile 10,13,68,72,9199 , 3 index partner 47,49,88 , 3 campaign 46,47,76 , 2 workplace 100,101 , 20 facility VCT 52,54,61,64,81,88,89,92,93,95,96,98,102107 , and 13 facility PITC 58,60,82–84,86,99,108113 (Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
“…HIVST could utilize this less restrictive policy space by developing creative solutions for the lack of formal or in-person counselling. Alternative solutions could include the provision of toll-free numbers for counselling and linkage to care [28,31,43], the delivery of testing instructions, messages, information and counselling via the internet or via a mobile phone application [23,25,31,40]. …”
Section: Discussionmentioning
confidence: 99%
“…As early as 2005, it was reported that health workers in Sub-Saharan Africa were self-testing for HIV, particularly where they were concerned about confidentiality [203]. Self-testing is a process in which an individual, who wants to know his or her status collects a specimen, performs a test and interprets the result themselves, often in private.…”
Section: Self-testingmentioning
confidence: 99%